The Denver developmental screening test: normative data for Ankara children - Yalaz, Kalbiye; Epir, Shirley (The Turkish Journal of Pediatrics, 1983)
Normative data were collected from a total of 1176 normal children, 596 boys and 580 girls living in Metropolitan Ankara, for a Turkish standardization of the Denver Developmental Screening Test. Data were summarized in tables and final test forms.
Keywords: Denver Developmental Screening Test (DDST); Turkish children